N-methyl-d-aspartate receptors and glycinergic transmission, respectively, mediate muscle relaxation and immobility of pentobarbital in mice. (1st April 2023) - Mukai, Akari; Irifune, Masahiro; Shimizu, Yoshitaka; Doi, Mitsuru; Kikuchi, Yuka; Katayama, Sotaro; Oue, Kana; Yoshida, Mitsuhiro; Ago, Yukio; Okada, Yoshiyuki; Morioka, Norimitsu; Nakata, Yoshihiro; et al.
Highlights: The components of anesthesia muscle relaxation, unconsciousness, and immobility were examined by grip strength, righting reflex, and the loss of motor response in mice. The change in each behavior induced by pentobarbital was roughly consistent with that in EEG and EMG power. A low dose of the indirect GABA receptor agonist gabaculine alone did not affect these components, but it enhanced all components induced by pentobarbital. This suggests that pentobarbital-induced components of anesthesia are mediated by GABAergic neurons. Moreover, muscle relaxation or immobility induced by the agent might be partially involved in NMDA receptor antagonism or glycinergic neuron activation, respectively. Abstract: Pentobarbital-induced anesthesia is believed to be mediated by enhancement of the inhibitory action of γ-aminobutyric acid (GABA)ergic neurons in the central nervous system. However, it is unclear whether all components of anesthesia induced by pentobarbital, such as muscle relaxation, unconsciousness, and immobility in response to noxious stimuli, are mediated only through GABAergic neurons. Thus, we examined whether the indirect GABA and glycine receptor agonists gabaculine and sarcosine, respectively, the neuronal nicotinic acetylcholine receptor antagonist mecamylamine, or the N-methyl-d -aspartate receptor channel blocker MK-801 could enhance pentobarbital-induced components of anesthesia. Muscle relaxation, unconsciousness, and immobility were evaluated by grip strength, the righting reflex, and loss of movement in response to nociceptive tail clamping, respectively, in mice. Pentobarbital reduced grip strength, impaired the righting reflex, and induced immobility in a dose-dependent manner. The change in each behavior induced by pentobarbital was roughly consistent with that in electroencephalographic power. A low dose of gabaculine, which significantly increased endogenous GABA levels in the central nervous system but had no effect on behaviors alone, potentiated muscle relaxation, unconsciousness, and immobility induced by low pentobarbital doses. A low dose of MK-801 augmented only the masked muscle-relaxing effects of pentobarbital among these components. Sarcosine enhanced only pentobarbital-induced immobility. Conversely, mecamylamine had no effect on any behavior. These findings suggest that each component of anesthesia induced by pentobarbital is mediated through GABAergic neurons and that pentobarbital-induced muscle relaxation and immobility may partially be associated with N-methyl-d -aspartate receptor antagonism and glycinergic neuron activation, respectively.